2019
DOI: 10.1111/febs.14838
|View full text |Cite
|
Sign up to set email alerts
|

Age‐induced oxidative stress impairs adipogenesis and thermogenesis in brown fat

Abstract: It is well‐established that the mass and function of human brown adipose tissue (BAT) declines with age. A key factor involved in age‐related impairment of BAT is oxidative stress; however, there is a paucity of studies to date that have explored this relationship. Here, we characterized the age‐related molecular and functional alterations in BAT in vivo in mice of different ages, and treated human brown adipocytes with H2O2 to dissect the direct effect of oxidative stress in vitro. We further explored the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…Chouchani et al (34) demonstrated a critical role for increased mitochondrial ROS generation in activation of UCP1 and subsequent thermogenic energy expenditure of BAT with cold exposure. However, increased oxidative stress has also been associated with the impairment of adipogenesis and thermogenesis in BAT during aging (35). Like white adipocytes, brown fat cells are prone to becoming dysfunctional when challenged with excess nutrients and ROS (36).…”
Section: Discussionmentioning
confidence: 99%
“…Chouchani et al (34) demonstrated a critical role for increased mitochondrial ROS generation in activation of UCP1 and subsequent thermogenic energy expenditure of BAT with cold exposure. However, increased oxidative stress has also been associated with the impairment of adipogenesis and thermogenesis in BAT during aging (35). Like white adipocytes, brown fat cells are prone to becoming dysfunctional when challenged with excess nutrients and ROS (36).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, the largest depot of BAT can be found in the supraclavicular region [56,58,59]. Fifty grams of BAT mass accounts for 3% to 5% of a human subject's basal metabolic rate [60]. In mice, BAT differs anatomically from human BAT because it is concentrated in specific depots (e.g., the interscapular depot), whereas in humans, brown adipocytes tend to be dispersed within white adipose depots.…”
Section: Brown White and Beige Adipose Tissuementioning
confidence: 99%
“…This caused a decline in BAT cells. Importantly, it was also shown that antioxidant treatment reduced the effects of oxidative stress and reversed BAT activity decline [60]. Mitochondrial dysfunction can develop during aging, causing a decrease in fuel oxidation overall and a buildup of reactive oxidative species [60].…”
Section: Oxidative Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…lipid metabolism, respectively. WAT is essential for energy storage and regulation of energy homeostasis, while BAT is characterized by thermogenesis and energy expenditure [6,7]. Interestingly, in the presence of certain stimuli, WAT can be transformed into BAT, this process is called browning [8].…”
Section: Introductionmentioning
confidence: 99%